1975
DOI: 10.1097/00000658-197507000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Human skeletal Muscle Energy Metabolism During and after Complete Tourniquet Ischemia

Abstract: The extent of cellular metabolic deterioration and its reversibility was studied on human skeletal muscle needle biopsies during operations in bloodless field. The tissue levels of high energy phosphates and glycolytic metabolites were analyzed after various times of tourniquet ischemia and compared to contralateral control extremity levels. In the ischemic extremity the phosphocreatine (CrP) levels decreased by 40% within 30-60 min and after 60-90 min a 60% reduction was found. No significant ATP changes occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 16 publications
6
48
0
1
Order By: Relevance
“…[22][23][24][25] We suspect, in addition, that physicians have been falsely reassured by tourniquet studies, which have suggested that muscle can tolerate up to 3 hours of ischemia. [15][16][17][18] However, tourniquet-induced ischemia may be less damaging than ACS-induced ischemia. In the only study to address this possibility, Heppenstal and associates 16 found that pH and phosphocreatine recovered rapidly and fully in dogs subjected to tourniquet-ischemia, but only slowly and partially in ACS-induced ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] We suspect, in addition, that physicians have been falsely reassured by tourniquet studies, which have suggested that muscle can tolerate up to 3 hours of ischemia. [15][16][17][18] However, tourniquet-induced ischemia may be less damaging than ACS-induced ischemia. In the only study to address this possibility, Heppenstal and associates 16 found that pH and phosphocreatine recovered rapidly and fully in dogs subjected to tourniquet-ischemia, but only slowly and partially in ACS-induced ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Current knowledge of muscle ischemia tolerance is derived from tourniquet-induced ischemia models, which suggest that muscle can tolerate up to 3 hours of ischemia before necrosis ensues. [15][16][17][18] However, a recent McGill University study of 76 patients who underwent fasciotomy 19 estimated that 35% of all ACS patients and 72% of those who developed necrosis did so within 2 hours of injury -earlier than the 3-hour safe period suggested by ischemia models.…”
Section: Introductionmentioning
confidence: 99%
“…This energy is provided by ATP molecules, for which storage is limited (ϳ35-55 mol/mg protein) (2,64,66).…”
Section: Mitochondria the "Powerhouse" Of The Cellsmentioning
confidence: 99%
“…Skeletal muscle can increase its ATP turnover, allowing it to transition from rest to exercise/ contractile activity, where different energy-producing substrates (high-energy phosphate compounds, glucose, glycogen, and lipids) can be oxidized (49,66,84,135). The most concentrated substrates in skeletal muscle are glycogen and phosphocreatine (PCr) (192), with higher PCr levels in glycolytic muscles (26).…”
Section: Mitochondria the "Powerhouse" Of The Cellsmentioning
confidence: 99%
“…The venous blood supply from ischaemic limbs in man shows a significant fall in Po, and pH after 30 minutes whilst the Pco, is raised (Wilgis 1971). Other studies in man have demonstrated a reduction of muscle phosphocreatine and a rise in lactate levels after 30 minutes; however, the amount of ATP shows no marked change after 90 minutes (Haljamae & Enger 1975). Paul (1961) found a block in neuromuscular transmission after 13 minutes in a rat muscle nerve preparation subject to anoxia, whilst the muscle fibres of the preparation remained sensitive to direct electrical stimulation for 40 minutes.…”
mentioning
confidence: 94%